Distribution, reproductive and energetic conditions of decapod crustaceans along the Scotia Arc (Southern Ocean) - Gustavo A. Lovrich; M. Carolina Romero; Federico Tapella; Sven Thatje (Scientia Marina, 2005)
Studies on decapod distribution patterns and reproductive and energetic conditions were carried out along the islands and shallows of the Scotia Arc (Southern Ocean) during the RV “Polarstern” LAMPOS expedition (ANT XIX/5) between April and May 2002. A clear biogeographic zonation was found. The Subantarctic Magellan-South Atlantic decapod fauna consisting of both “natant” (caridean) and “reptant” (astacidean, anomuran, and brachyuran) decapods appeared along the northern branch of the Scotia Arc to South Georgia, where Subantarctic and Antarctic faunas were found overlapping. An impoverished caridean shrimp fauna was found along the islands of the southern branch, from the South Sandwich Islands to the Antarctic Peninsula. Differences in the reproductive traits of the two most abundant species were detected. The reproductive cycle of Notocrangon antarcticus at South Georgia was more advanced than that at the South Orkney Islands, probably due to temperature differences between the two locations. Although the oogenesis and the reproductive cycle of Munida subrugosa seem to be in phase at Burdwood Bank and in the Beagle Channel, the oocyte number is probably lower at the former location. A new index was used to measure the energy devoted to reproduction by relating the energy contents of the egg mass/ovary plus hepatopancreas and the energy content of the whole body. This index revealed that the energy investment in reproduction was (1) independent of the sampling location, (2) species-specific, and (3) larger in caridean shrimps than in galatheid crabs.